An ecological study of three beach areas in Oton, Iloilo - Mascarinas, Mater (Gamboa) 1932- (s.n.], 1973)
This paper is an ecological study of three beach sites located at Oton, Iloilo. It attempts to show the richness and diversity of a marine beach community which constitutes a natural biotic community. It aims to present and describe the biotic and abiotic components of the beach during the months of June and July 1973.